2019
DOI: 10.15835/nbha47411561
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhiza Regulates Signal Substance Levels and Pathogen Defense Gene Expression to Resist Citrus Canker

Abstract: Citrus canker is a quarantined disease, severely harming citrus plants. Soil beneficial arbuscular mycorrhizal fungi (AMF) can provide a biological control pathway to resist pathogens. This work was to test changes of signal substances including hydrogen peroxide (H2O2), nitric oxide (NO), calmodulin (CaM), salicylic acid (SA) and jasmonic acid (JA) and the pathogen defense gene expression in roots of AMF (Paraglomus occultum) and non-AMF trifoliate orange (Poncirus trifoliata) seedlings after infected by a ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…These phenolics are synthesized in higher quantity due to the upregulation of signaling pathways involving hydrogen peroxide, salicylic acid, and nitrogen oxide pathways in the colonized roots [169]. Similar upregulation of these pathways was observed in the mycorrhizal inoculated plants against citrus canker [161]. Furthermore, elevated flavonoid content corresponded with increased resistance against the tomato mosaic virus in the mycorrhizal tomato plants [170].…”
Section: Effect Of Amf On Secondary Metabolites Under Biotic/abiotic Stressesmentioning
confidence: 69%
See 1 more Smart Citation
“…These phenolics are synthesized in higher quantity due to the upregulation of signaling pathways involving hydrogen peroxide, salicylic acid, and nitrogen oxide pathways in the colonized roots [169]. Similar upregulation of these pathways was observed in the mycorrhizal inoculated plants against citrus canker [161]. Furthermore, elevated flavonoid content corresponded with increased resistance against the tomato mosaic virus in the mycorrhizal tomato plants [170].…”
Section: Effect Of Amf On Secondary Metabolites Under Biotic/abiotic Stressesmentioning
confidence: 69%
“…AMF provides resistance against many biotic and abiotic stresses [ 108 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 ]. Phenolic compounds are important secondary metabolites in disease suppression or defense mechanisms against other stress.…”
Section: Secondary Metabolitesmentioning
confidence: 99%
“…Recently, research was carried out by the use of soil microbes to mitigate the negative impact of water deficiency. Arbuscular mycorrhizal (AM) fungi occurring widely in the soil can associate with the root of most plant species and this symbiosis can improve the plant performance under various environmental stresses (Augé, 2001) and may be able to augment plant tolerance to root herbivory and pathogens (Frew et al, 2020;Frew and Price, 2019;Xie et al, 2019;) and improve the soil structure (Rillig et al, 2015;. Many studies established that arbuscular mycorrhiza fungi improve the nutrient and water uptake of plants (Subramanian et al, 2006;Candido et al, 2015) mitigate the detrimental effect of stresses by increasing photosynthesis and productivity (Ruiz-Sánchez et al, 2010;Ebrahim and Saleem, 2017) and improve the yield quality (Salvioli et al, 2008;Hart et al, 2015;Bona et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, very few studies described improved defense mechanisms in mycorrhized citrus trees under biotic stress. Some studies suggested that mycorrhized citrus can better resist infection with citrus canker Xantomonas axonopodis (Xie et al, 2019). Mycorrhized Poncirus trifoliata rapidly activates SA-dependent signaling, such as through the genes PtEPS1 and PtPR4, thus ameliorating adverse effects of infection such as H 2 O 2 reduction and SA suppression by bacteria (Xie et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggested that mycorrhized citrus can better resist infection with citrus canker Xantomonas axonopodis (Xie et al, 2019). Mycorrhized Poncirus trifoliata rapidly activates SA-dependent signaling, such as through the genes PtEPS1 and PtPR4, thus ameliorating adverse effects of infection such as H 2 O 2 reduction and SA suppression by bacteria (Xie et al, 2019). Infected mycorrhized plants respond by enhancing SA signaling, which is transferred through common mycorrhizal networks to neighboring plants (Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%